System dynamics modeling to urban water-supply systems - Hao, Yiou. (2010)
Water has accompanied the development of mankind for almost the entire history; the increasing demand of water from the urban areas has leveled up the provision of urban water to a new high of engineering and urban planning science. The strong system of Roman aqueducts have been supplying the contemporarily world‘s largest city Rome with hundred million gallons of fresh water, and firmly secured the prosperous development in trading, manufacturing, gold mining and military activities. Today, our earth has born more huge scaled urban areas, they come in larger geological scales, accommodate more intensive population and become home to more human activities (business, service, tourism, technology etc). Thus a more informative and mighty plan of urban water supply must be drawn to meet the demand of these highly developed urban areas for long time.